What is not known is not aimed for — Understanding staff knowledge and readiness to embrace sustainable and healthy food - Elena Cavagnaro; Michel Altan; Ernst Jonker; Machiel Reinders (Research in Hospitality Management)
To mitigate the adverse effects of excessive consumption of animal proteins on both the environment and human well-being, a transition is needed toward plant-based proteins. Such a shift requires a change in eating behaviours, both at home and elsewhere. Focusing on hospitality and leisure settings, the aim of this study is threefold: firstly, to evaluate the alignment between the organisational policies and support mechanisms on one side and employees’ beliefs and daily experiences towards healthy and sustainable food on the other; secondly, to explore the staff’s readiness to embrace the protein transition using the stages of change model; and thirdly, to outline the prerequisites needed to ensure that employees show healthy and sustainable food behaviour drawing upon the COM-B model (motivation, opportunity, and capability for behavioural interventions) and the behaviour change wheel. Findings from a multi-case-study approach, which utilises a combination of research methods, suggest that employees across all cases exhibit a limited degree of readiness. Moreover, while the motivation to shift toward more healthy and sustainable food is high, capability and opportunity are rated low. To address this, various intervention strategies tailored to the context of hospitality and leisure are proposed that are pertinent to the cases under investigation.